2023
DOI: 10.1113/ep090988
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondria in the peri‐implant microenvironment

Abstract: New Findings What is the topic of this review?In this review, we consider the key role of mitochondria in the peri‐implant milieu, including the regulation of mitochondrial reactive oxygen species and mitochondrial metabolism in angiogenesis, the polarization of macrophage immune responses, and bone formation and bone resorption during osseointegration. What advances does it highlight?Mitochondria contribute to the behaviours of peri‐implant cell lines based on metabolic and reactive oxygen species signalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…28 Afterward, the large volume of woven bone is remodeled and replaced by the lamellar bone around the implant. 29 At that time, the implant was characterized by a thin seam of newly formed bone tissue lining their surface, and spaces of tissue lining their surface, and space of provisional connective tissue could be observed in the compartments between the threads. 11 The most significant challenge for this early stage is obtaining the fixation of the implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Afterward, the large volume of woven bone is remodeled and replaced by the lamellar bone around the implant. 29 At that time, the implant was characterized by a thin seam of newly formed bone tissue lining their surface, and spaces of tissue lining their surface, and space of provisional connective tissue could be observed in the compartments between the threads. 11 The most significant challenge for this early stage is obtaining the fixation of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…The trabecular bone fills the gap between the implant and the host bone. 29 While mechanical fixation is achieved at the cortical bone, avoiding excessive micromotions affecting fibrin tissue and impairing vascularity in the initial bone healing is essential. However, balance in osteoimmune regulation is an important factor for dental implant longevity, including protection from bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophilin D knockout mice, a genetic model of high oxidative metabolism, showed greater osseointegration in the spinal fusion site [34]. The role of implant materials to regulate mitochondrial activity in the peri-implant microenvironment has gained recent attention [35]. In the present study, the functional enrichment analysis of the RNA sequencing data revealed that SiN stimulated the upregulation of mitochondrial oxidative phosphorylation-related gene clusters over MTi and ATi materials (Figure 3) whereas osteogenic differentiation-related genes were not modulated by these materials (Figure 2).…”
Section: Discussionmentioning
confidence: 99%